The Effect of Educational Scaffolding Strategy in Teaching ‎Science in the Development of Inductive Thinking and the ‎Acquisition of Problem- Solving Skills - Tannous , Intesar; Alkhateeb, Linda (Jordan Journal of Educational Sciences, 2019)
The study aimed to investigate the effect of the educational scaffolding strategy in teaching science in the development of inductive thinking and acquiring problem- solving skills among sixth grade female students in Madaba Governorate. The sample of the study consisted of (50) female students, randomly assigned to two groups: The experimental group (N=26) was taught the science content by an educational scaffolding strategy, and a controlled group (N=24) was taught by the conventional method. To achieve the study aims, a teacher guide based on educational scaffolding strategy was prepared, and two instruments were developed: An inductive thinking test and a problem solving skills test, and were applied to the experimental and control groups, after verifying their validity and reliability. The study data were Analyzed by ANCOVA method. Results revealed statistically significant differences at (α=0.05) between the means of the experimental group and the control group on both scales of inductive thinking and problem solving skills, in favor of the experimental group.